Rearticulating Amar Ma'ruf Nahi Munkar as Emancipatory Social Counseling: A Foundation for Transformative Anti-Oppression Theology - Nadila Az’zahra; Nilna Izzah Afkarina; Aminatuz Zuhriyah; Ali Hasan Siswanto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The persistence of oppression in contemporary society, manifested in structural inequality, cultural domination, and epistemic marginalization, demonstrates the failure of normative theological approaches to bring about substantive social change. Although the concept of enjoining good and forbidding evil theologically possesses emancipatory potential, its practice remains trapped within a moralistic-formalistic framework and has not yet been operationalized as a mechanism for systemic social transformation. The research gap lies in the absence of an integrative model that connects theological, psychological, and sociological dimensions within a framework of liberation praxis. This study aims to rearticulate enjoining good and forbidding evil as a paradigm for emancipatory social counseling within a transformative theological framework. The theoretical approach employed is interdisciplinary, integrating Islamic theology, critical social philosophy, and emancipatory counseling theory. The research method employed is qualitative with a conceptual-philosophical approach through critical and hermeneutic analysis of classical and contemporary sources. The main argument of this research asserts that enjoining good and forbidding evil can be reconstructed as a social counseling process that functions not only as moral control but also as a mechanism for critical awareness, internalization of prophetic values, and transformation of oppressive social structures. Thus, theology no longer remains normative but functions as a liberating, practical force.